Does Marital Status Influence Levels of Anxiety and Depression Before Palliative Radiotherapy? - NIEDER, CARSTEN (In Vivo, 2018)
Background/Aim: To evaluate whether or not single patients report increased levels of anxiety and depression, compared to married or partnered patients scheduled to receive palliative radiotherapy. In principle, different levels of social support might cause such disparities. Patients and Methods: Retrospective comparison of two groups of patients (28% single, overall 100 patients), who scored their symptoms before palliative radiotherapy with the Edmonton symptom assessment system (ESAS). Results: The two groups differed significantly with regard to irradiated target sites (more brain irradiation in the married/partnered group), receipt of systemic therapy, which was more common in the married/partnered group, and mean age (single patients were older). Mean anxiety and depression scores were not significantly different between the two groups. Survival was similar, too (median 6 months, p=0.77). Conclusion: Similar ESAS scores of anxiety and depression were observed in the two groups (single vs. married/partnered patients).